2020
DOI: 10.1039/d0cc02451a
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray fluorescence microscopy reveals that rhenium(i) tricarbonyl isonitrile complexes remain intact in vitro

Abstract: An endoplasmic reticulum stress-inducing rhenium isonitrile complex was investigated for its axial ligand stability in living cells using X-ray fluorescence microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 46 publications
1
35
0
1
Order By: Relevance
“…295 Non-metal exogenous elements (e.g. Br or I, low natural abundance) can also be employed to monitor the intracellular fate of metallodrugs by XRF, as demonstrated for Br-labeled Pt agents (Pt19 †, Pt20 †) and I-labelled rhenium (Re3 †) complexes in vitro, 296,297 through a dual-mapping approach.…”
mentioning
confidence: 99%
“…295 Non-metal exogenous elements (e.g. Br or I, low natural abundance) can also be employed to monitor the intracellular fate of metallodrugs by XRF, as demonstrated for Br-labeled Pt agents (Pt19 †, Pt20 †) and I-labelled rhenium (Re3 †) complexes in vitro, 296,297 through a dual-mapping approach.…”
mentioning
confidence: 99%
“…However, caution should be exercised in interpreting localization of these compounds based on fluorescence microscopy because the photoluminescence of the rhenium tricarbonyl complexes is highly sensitive to environmental factors. For example, previous studies have shown how intracellular localization of rhenium tricarbonyl complexes as determined by inductively coupled plasma mass spectrometry (ICP-MS) and optical emission spectroscopy (ICP-OES) does not match that obtained via fluorescence microscopy. ,,, For these TRIP complexes, we have recently confirmed their cytosolic localization using XRF, demonstrating that in this case fluorescence microscopy works well for predicting their distribution in cells . Furthermore, these XRF studies were used to verify that the axial ligands remain bound to the Re center within cells, showing the remarkable stabilities of these complexes.…”
Section: Resultsmentioning
confidence: 84%
“…This complex induces apoptosis by increasing the unfolded protein burden and triggering ER stress. Furthermore, we have used X-ray fluorescence (XRF) microscopy to verify that these complexes are highly stable in cells, and we have developed an ovarian cancer cell line that is resistant to TRIP, which is a consequence of enhanced expression of drug efflux transporters and metallothioneins by these cells …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wilson's group has made a series of efforts to reveal the SARs, stability and mechanisms of rhenium complexes. 81,[84][85][86][87] The distribution and metabolism of drugs in vivo are very important issues for their potential clinical applications. However, few non-platinum-based metallo-anticancer agents have been studied in this aspect.…”
Section: Theranostic Applications Of Rhenium Complexesmentioning
confidence: 99%
“…Moreover, X-ray fluorescence microscopy shows that 52 is highly stable in vitro . 86 52 shows strong anticancer activity on a variety of cell lines in vitro and can inhibit A2780 ovarian cancer xenografts and prolong mouse survival in vivo . 52 shows partial colocalization with the LysoTracker Red dye and GalT-dsRed fusion protein.…”
Section: Theranostic Applications Of Rhenium Complexesmentioning
confidence: 99%